Evaluation of the knowledge of dental trauma in academic students of pedagogy and physical education courses - Jéssica Giovani da SILVA; Érika Campos NEVES; Sabrina Martins dos SANTOS; Maria Helena Monteiro de Barros MIOTTO (Universidade Estadual Paulista, 2022)
Abstract Introduction Dental trauma is considered a public health problem, being the second most prominent dental emergency, whose greatest occurrence is in schools, assigning teachers the responsibility of administering first aid. Objective To evaluate the knowledge of dental trauma among final-year's students of pedagogy and physical education courses at the Federal University of Espírito Santo. Material and method A cross-sectional descriptive study was applied. A total of 106 questionnaires were answered by 55 students from the physical education course and 51, from the pedagogy course; comprised of socio-demographic data and knowledge of dental injuries. Statistical analysis was done using the statistical package SPSS 20. Result 98.1% of the interviewees had no training on trauma, 92.5% considered themselves incapable of providing help when facing trauma, but considered the ability important (55.7%). When asked about tooth avulsion, most of them answered that they would not reimplant the tooth, were not aware of the appropriate time window to do so, or how the storage/transportation of the dental element was to be done. Conclusion These future teachers showed unpreparedness and deficient knowledge regarding trauma treatment procedures, favoring unfavorable prognoses which would negatively impact the quality of life of the victims in terms of aesthetic, functional and psychological aspects. Therefore, the need for dental trauma education during their professional training is evident.